Improving functional outcome and quality of life for patients with metastatic lesion of acetabulum undergoing cement augmentation. Issue 36 (September 2019) - Yan, Taiqiang; Zhao, Zhiqing; Tang, Xiaodong; Guo, Wei; Yang, Rongli; Tang, Shun; Dong, Sen
Abstract : Abstract: There is an increased enthusiasm in treating osteolytic metastatic acetabulum via injecting polymethyl-methacrylate (PMMA) as a bone filler to provide pain relief and potential structural support. The aim of this respective study is to determine the function and quality of life improvement after cement acetabuloplasty. Thirty two patients underwent acetabular cement augmentation between May 2014 and March 2018 were respectively reviewed. Isolated percutaneous acetabuloplasty (PA) was performed in 15 patients (group A) while radiofrequency ablation with PA (RFA-PA) in 12 patients (group B). Together with PA, open reconstructive surgery on ipsilateral femur was performed in another 5 cases (group C). Pre- and posttreatment functional evaluation and quality of life (QoL) assessment were carried out. The average followup duration was 11.5 (range, 3–36) months. None of major complications occurred. 81.2% (26/32) of patients achieved complete pain relief. Reduction of pain intensity and improvement of functional status achieved significantly differences after treatment ( P  = .00). Significant improvement ( P  = .00) was observed in scales of global QoL and pain-related restrictions in daily activities. Both isolated PA and RFA-PA procedures were equally effective towards the improvement of function and quality of life ( P  > .05). Regarding 5 patients in group C, pain intensity decreased when loading the affected limb and they could walk with crutches or cane. Bone cement acetabuloplasty is an adequate and effective mini-invasive procedure to relieve pain, restore function, and enhance the quality of life of patients for as long as possible in metastatic patients with short life expectancy. Ipsilateral surgery appears to be safe and well tolerated.